System and method for multiphase flow metering accounting for dissolved gas - Henry, M; Casimiro, C; Tombs, M; Probst, A (2016)
A system for metering flow of a fluid has a vibratable flowtube for receiving a multiphase fluid flow. A driver is configured to vibrate the flowtube. A pair of sensors is positioned to detect movement of the flowtube at different locations on the flowtube. Pressure and temperature sensors are positioned to measure a pressure of the fluid. One or more processors are configured to use a phase difference between the sensor signals to determine a fluid flow rate through the flowtube. The one or more processors are further configured to determine an amount of dissolved gas in the multiphase fluid using the pressure, the temperature, and the relative amounts the multiple liquids in the multiphase fluid.